2017
DOI: 10.1097/md.0000000000007170
|View full text |Cite|
|
Sign up to set email alerts
|

Role of breast magnetic resonance imaging in predicting malignant invasion of the nipple-areolar complex

Abstract: In this study, we assessed the diagnostic accuracy of breast magnetic resonance imaging (MRI) for evaluation of malignant invasion of the nipple-areolar complex (NAC).Patients with primary operable breast cancer who underwent preoperative breast MRI and received surgery during January 2011 to December 2013 were collected. The accuracy and potential factors of MRI in predicting nipple invasion were evaluated by comparing preoperative MRI with postoperative histopathologic findings. The consistency of interobser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(52 reference statements)
1
5
0
2
Order By: Relevance
“…In the present study, abnormal unilateral nipple enhancement was the most important independent MRI predictor of malignant NAC invasion (odds ratio = 61.07, 95% CI 12.81-291.22, P < 0.001) (specificity = 97.8% and diagnostic accuracy = 87.2%). This in agreement with Liao et al [7] who stated that abnormal unilateral nipple enhancement was the most significant independent image predictor of malignant NAC invasion (odds ratio = 4.86, 95% CI 1.76-13.80, P ≤ .01). Also, our results are in agreement with a study performed by Lee et al [17], and they found that MR images displaying inhomogeneous and diffuse enhancement in areas of thickened skin and the parenchyma of the NAC were indicative of NAC invasion.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, abnormal unilateral nipple enhancement was the most important independent MRI predictor of malignant NAC invasion (odds ratio = 61.07, 95% CI 12.81-291.22, P < 0.001) (specificity = 97.8% and diagnostic accuracy = 87.2%). This in agreement with Liao et al [7] who stated that abnormal unilateral nipple enhancement was the most significant independent image predictor of malignant NAC invasion (odds ratio = 4.86, 95% CI 1.76-13.80, P ≤ .01). Also, our results are in agreement with a study performed by Lee et al [17], and they found that MR images displaying inhomogeneous and diffuse enhancement in areas of thickened skin and the parenchyma of the NAC were indicative of NAC invasion.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of malignant NAC invasion by underlying breast cancer varies in different studies from 5.6 to 24.6% [14][15][16]. One study showed that malignant invasion of the NAC by underlying breast [1,3,[7][8][9][10][11][12][13][14][15][16]. It was stated that both tumor nipple distance and abnormal enhancement extending from the tumor to the nipple base were the most important predictors of malignant NAC invasion on MRI [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article, “Role of breast magnetic resonance imaging in predicting malignant invasion of the nipple-areolar complex: Potential predictors and reliability between inter-observers”, [ 1 ] which appeared in Volume 96, Issue 28 of Medicine , Dr. Chiung-Ying Liao's named appeared incorrectly as Chun-Ying Liao.…”
mentioning
confidence: 99%